Involvement of the Ventrolateral Periaqueductal Gray Matter-Central Medial Thalamic Nucleus-Basolateral Amygdala Pathway in Neuropathic Pain Regulation of Rats - Yi Sun; Jian Wang; Shao-Hua Liang; Jun Ge; Ya-Cheng Lu; Jia-Ni Li; Yan-Bing Chen; Dao-Shu Luo; Hui Li; Yun-Qing Li; Yun-Qing Li; Yun-Qing Li; et al. (Frontiers Media S.A., 2020)
The central medial nucleus (CM), a prominent cell group of the intralaminar nuclei (ILN) of the thalamus, and the ventrolateral periaqueductal gray matter (vlPAG) are two major components of the medial pain system. Whether vlPAG and CM are input sources of nociceptive information to the basolateral amygdala (BLA) and whether they are involved in neuropathic pain regulation remain unclear. Clarifying the hierarchical organization of these subcortical nuclei (vlPAG, CM, and BLA) can enhance our understanding on the neural circuits for pain regulation. Behavioral test results showed that a CM lesion made by kainic acid (KA) injection could effectively alleviate mechanical hyperalgesia 4, 6, and 8 days after spared nerve injury (SNI) surgery, with the symptoms returning after 10 days. Morphological studies revealed that: (1) the CM received afferents from vlPAG and sent efferents to BLA, indicating that an indirect vlPAG-CM-BLA pathway exists; (2) such CM-BLA projections were primarily excitatory glutamatergic neurons as revealed by fluorescence in situ hybridization; (3) the fibers originated from the CM-formed close contacts with both excitatory and inhibitory neurons in the BLA; and (4) BLA-projecting CM neurons expressed Fos induced by SNI and formed close contacts with fibers from vlPAG, suggesting that the vlPAG-CM-BLA indirect pathway was activated in neuropathic pain conditions. Finally, the vlPAG-CM-BLA indirect pathway was further confirmed using anterograde and monosynaptic virus tracing investigation. In summary, our present results provide behavioral and morphological evidence that the indirect vlPAG-CM-BLA pathway might be a novel pain pathway involved in neuropathic pain regulation.